Evaluating the Effects of Consolidation of Macedonian Mobile Markets - Mamuchevska, Daniela; Trpeski, Predrag (EBES Publications, 2018)
significantly changed. The final goal of these changes was to increase competition in the telecoms industry, forcing operators to raise quality of services and reduce their prices. But on the other hand, as a result of the liberalization of the telecommunications market, application of new telecommunication technologies, and as well as the effects of regulatory pricing intervention, telecom operators are faced with shrinking revenues and profitability. Despite traffic growth in the period 2014-2018, revenue levels of telecom companies has remained stagnant. Therefore it is not a surprise the fact that over the period 2002 - 2015 a total of 1024 competition policy cases have arisen in EU telecoms markets, where more than a half are merger control cases. Results from a number of empirical studies for ex-post evaluation of merger decisions, suggest that a merger may have negative price effects and positive effects on investment transformed into better quality of services for consumers. Macedonian telecommunications market was not excluded from this trend of merging between mobile operators. The proposed merger between mobile operators VIP and ONE was cleared with remedies in July 2015. In the public, there is an open debate about the effects of this competition authority’s decision on consumer welfare and market performances. Hence, the main objective of this paper is to quantify the impact of the approved merger decision between the second and third mobile operators on market performance and consumer welfare in the Macedonian mobile market. For the purposes of this research, we applied reduced-form econometric methods using a difference-in-differences (DiD) approach, which is an established and widely used methodology in the ex-post evaluation studies. We compared the evolution of the market competition and performances indicators, both before and after the decision. As a control group we used mobile markets data of selected countries from South East Europe. Analysis Mason DataHub, Eurostat data, OECD, World Telecommunication/ICT Indicators database were the main data sources for our analysis. The key outcomes of this research study are particularly important for the regulatory authorities, in the period that is characterized by the introduction and implementation of costly innovations such as 4G and 5G services, and in a context where mobile operators are lobbing for a bigger market consolidation and for a more lenient merger control in order to be able to invest effectively.
Keywords: .Mobile Telecom Markets, Ex-Post Merger Evaluation, Consumer Welfare, Efficiency